2021
DOI: 10.1108/jes-06-2020-0307
|View full text |Cite
|
Sign up to set email alerts
|

GDP and population growth: Evidence of fractional cointegration with historical data from 1820 onwards

Abstract: PurposeUsing data from 1820 onwards in a group of seven countries, namely, Australia, Chile, Denmark, France, the UK, Italy and the USA, the authors investigate if there is a long-run equilibrium relationship between the two variables (GDP and population).Design/methodology/approachUsing fractional integration and cointegration methods, this paper deals with the analysis of the relationship between GDP and population using historical data.FindingsThe authors’ results show first that the two series are highly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…As Malthus assumes that unchecked population growth badly affects the economy and economic development. The negative correlation between population growth and inclusive growth by incorporating economic and social into it is also been highlighted by eminent studies in the past (Bucci, 2023;Bucci et al, 2021;Chowdhury & Hossain, 2018;Gil-Alana et al, 2022;Sebikabu et al, 2020). As the terms of trade (TOT) turn better with 1 per cent it significantly increases the inclusive growth by 2 per cent.…”
Section: The Inclusive Growth Modelmentioning
confidence: 98%
“…As Malthus assumes that unchecked population growth badly affects the economy and economic development. The negative correlation between population growth and inclusive growth by incorporating economic and social into it is also been highlighted by eminent studies in the past (Bucci, 2023;Bucci et al, 2021;Chowdhury & Hossain, 2018;Gil-Alana et al, 2022;Sebikabu et al, 2020). As the terms of trade (TOT) turn better with 1 per cent it significantly increases the inclusive growth by 2 per cent.…”
Section: The Inclusive Growth Modelmentioning
confidence: 98%
“…Birdsall (1988) investigated the relationship between economic development and population growth and showed the importance of migration and urbanisation as drivers of demographic change. Gil-Alana et al (2022) examined the same issue applying fractional integration and cointegration methods to historical data for Australia, Chile, Denmark, France, the UK, Italy, and the US from 1820 onwards. They found that the GDP and population series are highly persistent, but the evidence on the existence of a long-run equilibrium relationship linking these two variables is mixed, cointegration only holding in the cases of France, Italy and the UK.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the exception of Gil-Alana et al ( 2022), none of the above mentioned papers examines the degree of persistence of population data using a fractional integration approach. The present study applies the same method to historical data on the world population rather than on the population in individual countries as Gil-Alana et al (2022) do and thus provides novel evidence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gil‐Alana, Font, and Gil‐López (2021) have used it to analyse the long‐run equilibrium relationship between population and GDP. Solarin et al (2019) have used the same fractional integration methods to investigate the persistence of carbon footprints.…”
Section: Review Of the Literaturementioning
confidence: 99%